2015
DOI: 10.1016/j.molonc.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of circulating KRAS mutated DNA in plasma from patients with advanced pancreatic cancer

Abstract: Cell-free DNA cfDNA KRAS Pancreatic cancer Liquid biopsy A B S T R A C TWe used KRAS mutations to investigate the clinical relevance of circulating tumor DNA (ctDNA) measurements in patients with advanced pancreatic cancer. Fifty-three blood samples were collected from 14 prospectively recruited patients prior to chemotherapy (gemcitabine or FOLFIRINOX) and subsequently every month during treatment. Samples were processed by density centrifugation and plasma DNA isolation. A Peptideenucleic acideclamp PCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 49 publications
5
115
1
3
Order By: Relevance
“…EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27). KRAS gene alterations detected in cfDNA have also been used as prognostic biomarkers, mainly in colorectal and pancreatic cancer (28,29). However, their predictive and prognostic value in NSCLC remains undefined, and to an extent controversial, due to the relatively few studies performed.…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%
“…EGFR mutations have also been shown to be of prognostic and predictive value, and patients with an activating mutation in EGFR in cfDNA have been reported to respond significantly better to TKIs (27). KRAS gene alterations detected in cfDNA have also been used as prognostic biomarkers, mainly in colorectal and pancreatic cancer (28,29). However, their predictive and prognostic value in NSCLC remains undefined, and to an extent controversial, due to the relatively few studies performed.…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%
“…In addition, ctDNA detection appears to have a strong prognostic value in patients with PDAC, but validation of this finding is required . Lastly, it has been suggested that ctDNA is a surrogate marker for tumor burden, but very few studies have formally assessed the relationship between ctDNA quantity and 3D tumor volumes, and never in PDAC . As PDAC is comprised of dense desmoplastic stroma with comparatively few tumor cells, the relationship between tumor volume and ctDNA quantity is difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…10.2 months, P < 0.001) (Chen et al ., ). Furthermore, it has been reported that high amount of cfDNA is a relevant prognostic marker for pancreatic cancer patients (Singh et al ., ; Tjensvoll et al ., ). A recent meta‐analysis by Creemers et al .…”
Section: Clinical Application Of Ctdna In Pdacmentioning
confidence: 99%